Demorest's Family Magazine - Demorest, William Jennings (New York: W.J. Demorest, 1886)
Demorest's Family Magazine . March 1886. A Quaint Cuban City -- The Other Persons: Chapter 7-9 -- Sianconset -- The Muezzin -- The Two Esthers -- Two Kings -- Flower Girl Pompeii -- "True Love Never did Run Smooth" -- Eventide -- The "Ketchup Ring" -- Early Spring -- Convenience and Ornament -- Home Art and Home Comfort: China Painting at home -- Cottage Design -- From Pencil to Brush -- " Ear Hath not Heard" -- A Woman's Club -- Optimism -- The World's Progress In the Arts, Sciences and Literature: Current Topics, Notes and Comments on Events of the Day. Intersecting Subjects and Notable Things which have Occurred During the Past Month, Contemporaneous History from a Familiar Point of View -- What Women are doing -- Kitchen: The Housekeepers Rut -- Scientific -- Diamonds of Thought -- Spice Box -- Mirror of Fashions: Furnishing in Style the Cosmopolitan Beau Ideal of Beauty and Elegance and the Perfection of Artistic Excellence -- Mme. Demorest's Portfolio of Fashions and what to Wear -- Fashionable Stationary -- Illustrated Fashions for Ladies -- Newmarkets and Jackets -- Materials for Early Spring -- Early Spring Millinery -- Wool Laces and how to Use Them -- Spring Dresses -- Fashionable Colors -- Torqueta Costume -- Ninita Basque -- New Laces, Embroideries and Braids -- New Materials for Mourning -- Combinations of Materials -- Ladies Aprons -- Underwear -- Misses Dresses -- Illustrated Fashions for children -- Ladies Club -- Pencil to Brush Club -- The Brinkley Collection: Of Antique Japanese and Chinese Keramics -- Art Notes -- The Responsibility of the Christian Church for the Liquor Traffic -- The Inspirations for Prohibition -- Latest Evolution of the Temperance Reform: President National Woman's Christian Temperance Union -- The Deacons Sunday-School Sermon -- The Criminality of a License -- "Pencil to Brush" -- Miss Frances E. Willard on Party Prohibition -- Review of New Publications -- An Earthly Paradise -- Swindlers -- Our Volume -- Something about Rain -- Business Notices
Demorest's New York Illustrated News Mme.; Demorest's Quarterly Mirror of Fashions
Keywords: Women's History; Slavery; Periodicals; Fashion; Serfdom; Cuba; Magazine; Island; Africans; Cooking